2022
DOI: 10.3390/ijerph192316054
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Personality on the Safety Behavior of Gold Mine Workers: A Moderated Mediation Approach

Abstract: Based on prior research on the relationship between personality and safety behavior, we construct a moderated mediation model that tests the effects of each of the Big Five personality traits (openness, conscientiousness, agreeableness, extraversion, and neuroticism) on the safety behavior of gold miners in Ghana. The model included safety competency as a mediator between the five personality traits and safety behavior. Management commitment to safety was used as a moderator to test the strength of the mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…While social media may expose users to conversations and content about safety, Lee and Shin (2017) contend that while social media may expose users to conversations and information about safety, it's important to take into account the larger context in which safety awareness is promoted. An individual's general awareness of safety is also greatly influenced by societal variables, personal experiences, and educational programs (Kang et al, 2019).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…While social media may expose users to conversations and content about safety, Lee and Shin (2017) contend that while social media may expose users to conversations and information about safety, it's important to take into account the larger context in which safety awareness is promoted. An individual's general awareness of safety is also greatly influenced by societal variables, personal experiences, and educational programs (Kang et al, 2019).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…According to Kang et al (2019), educational initiatives and personal experiences play a significant role in determining an individual's level of safety awareness. These elements work in concert to raise undergraduate students' understanding of safety.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…8 Based on the relationship between personality and safety behavior, Yang et al constructed a moderated mediation model and tests the effects of Big Five personality traits on the safety behavior of gold miners in Ghana. 9 Ma et al used the Myers-Briggs Type Indicator (MBTI) to explore the preliminary relationship between personality types of construction workers and unsafe behaviors. 10 Guo et al demonstrated the feasibility of using personality traits to predict the driving safety of high-speed train drivers, to better understand the relationship between the personality and driving safety in high-speed railway driving.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on the relationship between personality and safety behavior, Yang et al. constructed a moderated mediation model and tests the effects of Big Five personality traits on the safety behavior of gold miners in Ghana . Ma et al used the Myers-Briggs Type Indicator (MBTI) to explore the preliminary relationship between personality types of construction workers and unsafe behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, safety leadership had a substantial impact on safety culture, and in turn, safety culture significantly influenced safety performance [8]. Safety competency holds paramount importance across various industries, directly impacting both individual well-being and overall organizational success [9].…”
Section: Introductionmentioning
confidence: 99%